Traditional Chinese medicine use is associated with lower risk of pneumonia in patients with systemic lupus erythematosus: a population-based retrospective cohort study - Wang, Weijie; Wang, Yu-Hsun; Yang, Kepeng; Ye, Xiangsheng; Wang, Xinchang; Wei, James Cheng-Chung (Frontiers in Pharmacology, 2023)
Objectives: To investigate the association between traditional Chinese medicine (TCM) therapy and the risk of pneumonia in patients with systemic lupus erythematosus (SLE). Methods: This population-based control study analyzed the data retrieved from the National Health Insurance Research database in Taiwan. From a cohort of 2 million records of the 2000–2018 period, 9,714 newly diagnosed patients with SLE were initially included. Via 1:1 propensity score matching, 532 pneumonia and 532 non-pneumonia patients with SLE were matched using the parameters of age, sex, and SLE diagnosis year. The use of TCM therapy was considered from the SLE diagnosis date to the index date and the cumulative days of TCM therapy were used to calculate the dose effect. Conditional logistic regression was used to investigate the risk of pneumonia infection. Furthermore, to explore the severity of pneumonia in SLE, sensitivity analyses were performed after stratification using the parameters of emergency room visit, admission time, and antibiotic use. Results: TCM therapy for >60 days could significantly reduce the risk of pneumonia in patients with SLE (95% CI = 0.46–0.91; P = 0.012). Stratified analysis showed that TCM use also reduced the risk of pneumonia in younger and female patients with SLE by 34% and 35%, respectively. TCM for >60 days significantly reduced the risk of pneumonia in the follow-up periods of >2, >3, >7, and >8 years. In addition, the exposure of TCM for >60 days reduced the risk of pneumonia in patients with SLE who were treated with antibiotics for moderate or severe pneumonia. Finally, the use of formulae for tonifying the kidney for >90 days and use of activating blood circulation formulae for <30 days could substantially reduce the risk of pneumonia infection in patients with SLE. Conclusion: TCM use is associated with a lower risk of pneumonia among patients with SLE.